USING PORTFOLIO ASSESSMENT TO ENHANCE STUDENTS' SCIENCE PROCESS SKILLS IN STEM LEARNING ACTIVITIES - Shidiq, Galih Albarra; Bunnaen, Wutthisak; Widiyan, Agung Purwa (Jurnal Pendidikan Matematika dan IPA, 2024)
Using portfolio assessment to enhance students"™ science process skills was potentially impactful in the STEM learning activities. Its benefits to navigate students gaining comprehensive experiences is necessary. The objective of this study was to examine portfolio assessment in enhancing students' science process skills in STEM learning activities. A quantitative research approach was implemented, with a sample of 33 students between the ages of 14 and 16, drawn from Indonesian public senior high schools. The instrument used to collect the data was a test. It consisted of multiple-choice and open-ended questions. The data were analyzed by using descriptive statistics. The findings reveal key indicators of science process skills in STEM learning activities, identifying portfolios that influence students' engagement and understanding within the STEM learning activities. Importantly, this study highlights the critical role of encouraging students to ask questions, as it can significantly enhance their science process skills.